Switching time-invariant formation control of a collaborative multi-agent system using negative imaginary systems theory. (February 2020) - Tran, Vu Phi; Garratt, Matthew; Petersen, Ian R.
Abstract: The movement of cooperative robots in a densely cluttered environment may be impossible if the formation type is invariant. Hence, we investigate a novel method of switching time-invariant formation control for a group of heterogeneous autonomous vehicles, which may include Unmanned Ground Vehicles (UGV) and Unmanned Aerial Vehicles (UAV). We have extended a Negative Imaginary (NI) consensus control approach to switch the formation shape of the robots whilst only using the relative distances between agents, in combination with those between agents and obstacles. All agents can automatically create a new safe formation to overcome obstacles, then restore the prototype formation once the obstacles are cleared. We address the oscillation and local minima problems, generated by existing algorithms, using a newly developed circle fitting approach. We also highlight the advantages of our proposed algorithms over the kinematic controller and the conventional Artificial Potential Field (APF) controller from both theoretical and experimental standpoints. Simulation and experimental results are then analyzed to validate the feasibility of our proposed approach. Graphical abstract: Highlights: A novel Leader–Follower NI switching formation control law based on the relative-position consensus for networked robots moving in formation. Three comprehensive and effective obstacle avoidance strategies-based formation switches for a heterogeneous multi-robot system, considering even the various sizes of robots. The stability of complete formation-avoidance control architecture is proved. The homogeneity, synchronization, and simplification of the formation control, along with the obstacle avoidance is guaranteed based on a homogeneous NI framework. All performances of formation control and avoid obstacles are distributed. The main strength of our proposed method over others are verified through tests.